Hans Brinker, or, The silver skates - Dodge, Mary Mapes 1830-1905. (New York Aladdin Paperbacks, 2002)
A Dutch brother and sister work toward two goals--finding the doctor who can restore their father's memory and winning the competition for the silver skates.
"Includes reading group guide"--Cover.
Keywords: Brothers and sisters -- Fiction; Ice skating -- Fiction; Netherlands -- History -- 19th century -- Fiction